(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: Low birth weight (LBW) is an important risk factor that contributes to mortality of 15-20% of newborn globally. This case-control study was conducted to determine factors associated with low birth weight among new-born delivered at term in obstetrical and gynecological wards of the hospital. Patients and methods: Mothers of 150 low birth weight babies born at term were taken as cases and 150 normal weight babies born at same day, were taken as controls. Mothers were interviewed on using a semi-structured and pretested questionnaire. The data was analyzed on SPSS Version 22.0. A p-value <0.05 was considered statistically significant. Results: Illiterate mothers had 2.332 odds of having low birth weight babies (0.03, 95% CI = 1.3317 to 4.152). Mothers from low socio-economic status had 3.54 odds of delivering LBW (p-value = 0.000, 95% CI = 2.184 to 5.94). The odds of having low birth weight babies was 4.004 times high in the mothers exposed to passive smoking (p-value = 0.000, 95% CI = 2.477 to 6.474). Hemoglobin value less than 10 gm/dl was found to be significantly associated with odd of having LBW 3.003 in anemic mothers versus non anemic mothers (p-value = 0.0027, 95% CI = 1.279 to 3.227). Mother with parity <3 had 0.0933 odds of having low birth weight babies. Mothers having adequate antenatal care had 0.394 odds of having low birth weight babies. Conclusion: Illiteracy, low socio-economic status, employment, anemia, tobacco smoke exposure and inadequate antenatal care were significantly associated with LBW.